Eine ökonomische Analyse der Besteuerung außerordentlicher Einkünfte nach der Fünftelregelung unter besonderer Berücksichtigung des Progressionsvorbehalts - Hechtner, Frank (Betriebswirtschaftliche Forschung und Praxis, 2017)
This paper analyzes the economic effects when a taxpayer receives tax exempted (under progression reservation) and extraordinary income. In such a case, there are special rules (tax scales) how to calculate the overall tax burden. It turns out that in this case the requirements on a systematic tax scale are violated. It can be shown theoretically that tax rates over 100 % as well as negative tax rate can become effective. In a micro simulation on basis of individual tax statistics data from the Federal Statistical Office the paper analyzes to which extend taxpayers are affected by tax rates over 100 % or negative tax rates. Moreover, the amount of overall tax revenues from taxing extraordinary income is calculated.
CRIS-Team Scopus Importer:2020-08-10